Comparing the short-term therapeutic effects and safety profiles of rituximab therapy in pemphigus vulgaris patients either early treated or later than six months. (19th May 2019) - Balighi, Kamran; Daneshpazhooh, Maryam; Akbari, Zahra; Tavakolpour, Soheil; Azimi, Pourya; Azizpour, Arghavan
Abstract: Introduction: Rituximab is a recent treatment in recalcitrant pemphigus vulgaris (PV) patients. This study aims to establish the optimal time for rituximab therapy in PV patients. Methods: In this retrospective study, patients who received rituximab within six months of diagnosis were classified as the early treatment group, and patients who have received it later than six months were classified as the delayed treatment group. Results: Ninety-five PV patients were reviewed. Fourteen (14.8%) and 81 (85.2%) patients received rituximab within the first six-months from diagnosis and after that, respectively. In the former group, seven patients have received rituximab as the first-line therapy. The rate of complete remission off therapy (CR off therapy) was significantly higher in this early treatment group (92.9%) compared with the delayed treatment group (66.6%) ( p  = .47). The patients in early treated group significantly sooner achieved remission ( p  < .001) and it lasts for a longer time ( p  = .006). The relapse rate was also significantly lower in the early treatment group (five patients, 38.5%) compared with the delayed treatment group (54 patients, 71.1%) ( p  = .02). Conclusions: Early treatment with rituximab can lead to a higher rate of complete remission, a lower rate of disease relapse, and longer duration of complete remission in PV patients.